2005
DOI: 10.1080/00207450590958556
|View full text |Cite
|
Sign up to set email alerts
|

Age and Sex Differences in Neurobehavioral Performance: A Study of Portuguese Elementary School Children

Abstract: In this study normative data were obtained on measures of IQ, visual/motor, motor and memory functions among Portuguese elementary school children. Subjects were 228 females and 275 males, 8.0 to 11.9 years of age, in grades 2 through 4, who participated in a dental study. Performance on all tests improved with increasing age. Females performed better in rote verbal learning, psychomotor speed, and speed of information processing. Males had higher scores on tests of visual learning, visual memory, and fine mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
2
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 28 publications
4
32
2
2
Order By: Relevance
“…This pattern is similar to those reported in previous studies (e.g. Comalli et al, 1962;Ligon, 1932;Martins et al, 2005;Oliveira et al, 2016;Stroop, 1935) and may correlate with the maturation of children (Tamm, Menon, & Reiss, 2002). Younger children tend to get lower scores than older children in the Stroop Word and Stroop Color test because of their lower reading fluency and color identification, which progressively develops with age (Ligon, 1932).…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…This pattern is similar to those reported in previous studies (e.g. Comalli et al, 1962;Ligon, 1932;Martins et al, 2005;Oliveira et al, 2016;Stroop, 1935) and may correlate with the maturation of children (Tamm, Menon, & Reiss, 2002). Younger children tend to get lower scores than older children in the Stroop Word and Stroop Color test because of their lower reading fluency and color identification, which progressively develops with age (Ligon, 1932).…”
Section: Discussionsupporting
confidence: 77%
“…There is no consensus in the literature on the influence of sex on Stroop performance. Some studies like Martins et al (2005) found significant differences in favor of girls in all Stroop scores, while other studies such as Armengol (2002) did not report any differences. The same discrepancies occur in adults, with studies reporting a better performance in women than in men (Moering et al, 2004;Strickland, D'Elia, James, & Stein, 1997;Van der Elst et al, 2006) while others reported an inexistent effect of sex (Jensen & Rohwer, 1966;Ligon, 1932;Stroop, 1935).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Furthermore, male hormone levels seem to be negatively correlated with linguistic measures in boys (Christiansen & Knussmann, 1987). On the other hand, Martins et al (2005) suggested that social and educational trends that affect sexual development might contribute to gender differences in cognitive performance concerned with visuo-spatial skills, memory, executive functions, and also language (Halpern, 2000). Taken together, these factors might explain why girls generally outperform boys in several measures of language.…”
Section: Discussionmentioning
confidence: 97%